Analisis Kebutuhan Air Domestik Daerah Aliran Sungai Kampar (Studi Kasus: Pos Awlr Danau Bingkuang) - Syarifah Sophia Vinka Zafani; Bambang Sujatmoko; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The Tande River is a river that flows in the Tande watershed that passes through Daik Lingga Village, with a sub-watershed area of 765 ha. Generally, rivers in Lingga Regency flow in hilly areas so they are covered with forest plants and during the rainy season there are frequent overflows of several rivers. For this reason, as a river that has the potential to overflow, an analysis is carried out regarding the capacity of the Tande River. In order to carry out the simulation, the planned flood discharge at the 25-year return period was calculated using the Nakayasu Synthetic Unit Hydrograph method, with a flowrate of 40.333 m3/s as the result. The results of the calculation of the planned flood discharge in the 25 year return period is used as input to the simulation of the water level profile in the Tande river in the same period, using HEC-RAS 4.1.0. From the simulation results of the water level profile on the Tande River, the results obtained that the planned flood discharge for the 25 year return period overflowed in 24 cross sections with flood heights ranging from 14-46 cm. Keywords: tande river, return period flood discharge, surface height, HEC-RAS